The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/ejoc.201101121
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Method for the Copper‐Catalyzed Selective Synthesis of Diaryl Chalcogenides from Easily Available Chalcogen Sources

Abstract: An efficient protocol for copper-catalyzed C-S or C-Se bond formation between aryl iodides and easily available chalcogen sources leading to diaryl chalcogenides is reported. A variety of symmetrical diaryl sulfides and diaryl selenides were synthesized in good to excellent yields. Unsymmetrical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 75 publications
0
55
0
Order By: Relevance
“…43 Bis(4-(phenylethynyl)phenyl)sulfane (DPEDPS) was obtained via a Sonogashira coupling reaction of DBDPS with phenylacetylene in the presence of CuI and Pd(PPh 3 ) 4 as catalyst and diisopropylamine/toluene as solvent under an argon atmosphere. Bis(4-bromophenyl)sulfane (DBDPS) was synthesized via a copper-catalysed C-S bond forming reaction from 1-bromo-4-iodobenzene according to a literature procedure.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…43 Bis(4-(phenylethynyl)phenyl)sulfane (DPEDPS) was obtained via a Sonogashira coupling reaction of DBDPS with phenylacetylene in the presence of CuI and Pd(PPh 3 ) 4 as catalyst and diisopropylamine/toluene as solvent under an argon atmosphere. Bis(4-bromophenyl)sulfane (DBDPS) was synthesized via a copper-catalysed C-S bond forming reaction from 1-bromo-4-iodobenzene according to a literature procedure.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Other oxidants including CAN, PhI(OAc) 2 and benzoquinone did not afford the desired product (entries 7-9), while K 2 S 2 O 8 , TBHP or dicumyl peroxide (DCP) showed very low conversion (entries [10][11][12]. After evaluating the loading of the catalyst and oxidant (entries [13][14][15][16][17], the conditions were set as 2 equivalents of DTBP with 2 mol% of Mn(OAc) 2 (entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…10 Various sulfonyl hydrazide reagents have been developed in the sulfenylation of indoles, 11 aryl halides, 12 activated alkenes 13 and aryl acetylenes. 4 This new strategy could not only avoid smelling volatile sulfur sources such as thiols, 5 thiolates 6 and disulfides, 7 but also expend the limited substrate scope of agents like thiourea, 8 thiocyanate 9 and metal sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…85 Optimization studies showed that DMF and DMSO were suitable solvents for this reaction but toluene and ethylene glycol were ineffective. …”
Section: Na 2 S As the Sulfur Sourcementioning
confidence: 99%